Comparative phytoremediation potentials of Impatiens balsamina L. and Crotalaria retusa L. for soil contaminated with used lubricating oil - Sumudu Sriyanthi Walakulu Gamage; Kanaji Masakorala; Murray T Brown; Shirani Manel Kumari Widana Gamage (Environmental Advances, 2021)
Soil contaminated with used lubricant oil (ULO) has become an emerging environmental threat. Phytoremediation is a cost effective, environmentally friendly and novel technique with great potential for remediation of soils contaminated with used lubricating oil (ULO). Therefore, the aim of this study was to investigate the phytoremediation potentials of Crotalaria retusa L. and Impatiens balsamina for ULO contaminated soil. A randomized block pot experiment was conducted for each species under plant house conditions in soil contaminated with ULO at a concentration of 5,000 mg kg−1 (0.5% w/w)-30,000 mg kg−1 (3% w/w). The percentage biodegradation of ULO in the rhizosphere soil of both species following 90 days exposure indicated significant (p < 0.05) time dependent increases compared to the respective control carried out in contaminated soil without plants. Comparatively higher biodegradation of ULO was recorded from the rhizosphere of C. retusa L. than that of I. balsamina. The measured total microbial activity and cultivable population size of hydrocarbon utilizing bacteria (HUB) suggest that phytoremediation might have occurred mainly via rhizodegradation. The Allium cepa bioassay revealed the reduction of potential cytotoxicity and genotoxicity with the decrease of ULO in phytoremediated soils. The results further revealed significant (p<0.05) positive correlation of N−NO3−1, extractable P concentration and significant (p < 0.05) negative correlation of soil pH with percentage ULO degradation. Therefore, phytoremediation using the test plant species not only reduced ULO levels, cytotoxicity and genotoxicity but also improved overall soil quality. These results highlight the higher phytoremediation potential of C. retusa than that of I. balsamina for soil contaminated with ULO.